Diversification of angiosperm reproductive strategies predated the end-Cretaceous extinction - Jaemin Lee; Dori L. Contreras; James G. Saulsbury; Garland R. Upchurch; Cindy V. Looy (Science, 2026)
Angiosperm reproductive evolution is traditionally linked to the end-Cretaceous biotic crisis and subsequent ecological restructuring. Here, we report diverse and unexpectedly large diaspores (dispersal units) from an in situ late Campanian (74.6 million years ago) tropical forest from the Jose Creek Formation in New Mexico. Nearly 80 distinct diaspore morphotypes demonstrate that the flora had increased morphological specialization and an exceptionally large average and range of diaspore volume comparable to the Cenozoic records. These findings suggest that substantial increases in reproductive investment and specialization preceded the end-Cretaceous extinction. Our results indicate that Cretaceous angiosperms had already evolved diverse dispersal strategies, suggesting that animal-mediated dispersal and dense, angiosperm-integrated canopies were established far earlier than was previously recognized.